Glucosinolate content and myrosinase activity evolution in three maca (Lepidium meyenii Walp.) ecotypes during preharvest, harvest and postharvest drying - Yábar E. (2011)
The authors are thankful to Ecoandino s.a.c for the maca material. This research was supported by the Consejo Nacional de Ciencia y Tecnología (CONCYTEC), Peru.